PWE-025 Assessing the Percent of Days Linaclotide Improved Abdominal Symptoms and Stool Frequency in Patients with Irritable Bowel Syndrome with Constipation (IBS-C): Pooled Analysis of 2 Phase 3 Trials. (4th June 2013) - Rao, S S; Chang, L; Hao, X; Lavins, B; Shiff, S J; Cao, X; Schneier, H; Currie, M; Johnston, J
Abstract : Introduction: Linaclotide (LIN), a minimally absorbed guanylate cyclase C agonist (GCCA), improved abdominal symptoms and bowel movement (BM) frequency in patients (pts) with IBS-C in 2 Phase 3 trials. This post-hoc analysis determined the % of days pts reported improvements in abdominal symptoms and BMs with LIN or placebo (PBO) treatment. Methods: In 2 Phase 3 trials, pts with IBS-C (Rome II criteria) were randomised to LIN 290 -μg qd po or PBO. Using pooled intent-to-treat (ITT) data from the 1st 12 wks of both trials, we determined (for pts with an average baseline score ≥3 out of 10 for each respective parameter) 1) % of days with ≥30% improvement in either abdominal pain, discomfort, bloating, cramping or fullness and 2) % of days with a spontaneous BM (SBM) or a complete SBM (CSBM). Results: The pooled ITT population included 797 PBO- and 805 LIN-treated pts. During the 2-wk Baseline Period, pts had an SBM on a mean of 24% of days and a CSBM on a mean of 3% of days. Pts in subgroups with an average baseline abdominal symptom score ≥3 experienced ≥30% improvement in the specific abdominal symptom on a significantly greater % of days for LIN vs PBO (Table). LIN-treated pts had ≥30% improvement in abdominal pain for 55% of days vs 41% for PBO (p < 0.0001). Results were similar for other abdominal symptoms, with LIN-treated pts achieving ≥30% improvement for 50% of days during the Treatment Period; PBO pts met the threshold on 33–42% of days. LIN also significantly increased the % of days with SBM/CSBM vs PBO (Table). Conclusion: LIN improved abdominal symptoms (pain, discomfort, bloating, fullness and cramping) by ≥30% on 50% of treatment days and significantly increased the % of days with SBM/CSBM. Thus, LIN relieved key IBS-C symptoms and increased the % of days with symptom improvement. These data provide estimates for results of treatment with LIN that clinicians and pts may anticipate. Supported by Ironwood Pharmaceuticals Inc and by Forest Laboratories, Inc. Editing assistance was provided by Complete Medical Communications, funded by Almirall Disclosure of Interest: S. Rao Grant/Research Support from: SmartPill Corporation, Forest Laboratories and Ironwood Pharmaceuticals, Conflict with: Advisory board for Forest Laboratories and Ironwood Pharmaceuticals. Sits on Advisory Board Smart Pill Corporation, AMS, AstraZeneca and Asubio Pharmaceuticals, L. Chang Grant/Research Support from: Ironwood Pharmaceuticals and Forest Laboratories, Consultant for: Ironwood Pharmaceuticals and Forest Laboratories, X. Hao Shareholder of: Ironwood Pharmaceuticals, Employee of: Ironwood Pharmaceuticals, B. Lavins Shareholder of: Ironwood Pharmaceuticals, Employee of: Ironwood Pharmaceuticals, S. Shiff Shareholder of: Forest Laboratories, Employee of: Forest Laboratories, X. Cao Employee of: Forest Laboratories, H. Schneier Shareholder of: Forest Laboratories, Employee of: Forest Laboratories, M. Currie Shareholder of: Ironwood Pharmaceuticals, Employee of: Ironwood Pharmaceuticals, J. Johnston Shareholder of: Ironwood Pharmaceuticals, Employee of: Ironwood Pharmaceuticals